The Use of Contextual Models in Improving Student Learning Outcomes and Social Skills in Science Learning in Junior High Schools - Syofia Yohana (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
This Research is motivated by the low learning outcomes and low social skills of students in science learning. The reality in the field is that students experience difficulties in understanding concepts about inheritance material and the difficulty of students communicating, collaborating in discussion activities during learning. The aim of the research is to improve student learning outcomes and social skills in the matter of inheritance in natural science subjects. This study uses a contextual model with 2 cycles. Based on research results on the use of contextual models can improve learning outcomes and students' social skills in learning natural sciences at SMP Negeri 1 Percut Sei Tuan. This is evidenced by the acquisition of student learning outcomes increasing in each cycle and exceeding the Minimum Completeness Criteria (KKM) score limit of 75. The number of students who completed the first cycle was 18 students (5 6.25 %) and those who did not complete their studies 14 students (43.75 %). After making improvements in cycle II, the percentage of students' learning outcomes was increased by 87.50 % and only 4 students who had not finished with a percentage of 12.50 %. In cycle I students' social skills for aspects of working with friends 75%, aspects of showing social responsibility 62%, aspects of controlling emotions 40.63%, aspects of interacting with others 43.75%, aspects of participating 59.38%, cultivating sportsmanship, discipline and healthy living 51.56%. After implementing improvements in cycle II there was a significant increase in aspects of working with friends (95.31%), showing social responsibility (87.5%), controlling emotions (56.25%), interacting with other people (93.75 %), participating (82.81%), cultivating sportsmanship, discipline and healthy living (62.5%), writing opinions/ideas (73.44%), leading (70.31%).